EXPLORING THE EFFECTIVENESS OF THE ACEP CYCLE IN IMPROVING STUDENT WRITING SKILLS - Putri, Anindya Rahma; Gonzalez , Maria Fernanda (Top Educational Review Journal (TERJ), 2025)
The modification of the ACEP cycle is a pedagogical strategy consisting of four components: (A) Activities. (C) Classroom discussion. (E) Exercises. (P) Performance. The application of ACEP cycle modifications is used as a strategy to improve writing skills. This is the primary focus to consider in improving writing skills. The purpose of this study was to evaluate how effective the process of learning writing skills was by applying ACEP cycle modifications. This study used a mixed-methods approach. At the qualitative stage, an explanatory description design strategy is applied to collect comprehensive and in-depth information about the learning model applied by the teacher in the classroom. A pre- and post-test control group design is used in the quantitative stage. The average score of students using the ACEP cycle modification was 82.64, higher than that of students who studied under the demonstration learning model which was 80.03. This finding is reinforced by the result of the significance coefficient = 0.006 < 0.05 so H0 is rejected. Thus, there is a difference in average student learning outcomes between the modification of the ACEP cycle and the demonstration learning model. ACEP cycle modification has practical implications for writing skills. First, it can easily identify the initial condition of students’ writing skills. Second, ACEP cycle modification allows teachers to better understand how students build an understanding of writing concepts. Third, students can actively participate in the learning process and fourth, teachers can observe the construction stage and measure student progress more accurately